Synergistic Knowledge Networks In Innovative Alliances - Karolina CHRABĄSZCZ-SARAD; Anna KARAŚ (Communications of International Proceedings, 2021)
The development of an enterprise requires the use of knowledge and rare skills. These resources are often owned by other market players and enterprises’ external relationships are critical to the acquisition and creation of knowledge. In particular, strategic alliances with partners that bring additional intellectual value or in which this value is constructed to generate new ideas, products and organisational processes are becoming important. The knowledge necessary for innovative activity is complex, extensive and requires the development and distribution of the synergy of the knowledge network in the alliance. The aim of the article is to indicate the instruments and methods of knowledge management in the field of strategic alliance for the development of innovative activities of the enterprise and to present the results of empirical research – a case study. The following research methods were used to achieve the objectives of the work and to verify theses: analysis of the results of previous research, analysis of influence factors, interviews and a case study method to illustrate and emphasise the importance of alliances of heterogeneous knowledge networks as well as similar knowledge bases.
Keywords: innovative alliances; knowledge management; knowledge networks; synergy.